Zastosowanie Internetu w agrobiznesie - Winnicki, Piotr (The Internet in Agribusiness, 2007)
This article presents the Internet as the biggest and most useful tool for effective communication and data exchange between customers, producers and other entrepreneurs. It shows that e-business is available also in agribusiness and agricultural marketing. It also describes The Integrated Information System of Agricultural Market, developed by Polish government. The goal of this Internet service is recording and processing of agricultural market data (e.g. quantity of production, commodity prices) and presenting them in aggregate form.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 341-348